"The Soul of My Office": Lady Torrington's Leadership of the British Embassy in Brussels during the Belgian Revolution of 1789. Issue 5 (3rd September 2022) - Speeckaert, Jean-Charles
Abstract: This paper argues that Lady Lucy Boyle, Viscountess Torrington, effectively took the position of her husband George Byng, 4 th Viscount Torrington, Minister Plenipotentiary in Brussels from 1782 to 1792, during his absence in 1789. Pretending that his uncle needed him in England, Lord Torrington obtained permission to leave his post in the Austrian Netherlands in June. Lucy Boyle stayed with two embassy secretaries in Brussels until the end of November, a period of five months against the troubled background of the Revolution in Brabant. These months were the peak of the revolt of the Belgian provinces against Habsburg rule. Intended by her husband to arrange "presentation and letters of recommendation", Lady Torrington far exceeded that brief and defended the British residence against unwelcome incursion. She was the last to leave the embassy when the Austrian Government fell. This article highlights how a woman could assume a role that is normally linked to masculinity. Fiercely proud of his wife, whom he declared to be "the soul of my office", Lord Torrington was keen to speak about her active role in his reports to the Duke of Leeds. Lady Torrington and her two eldest daughters were considered as the leading lights of the British colony in Brussels. I outline the reception given to Lucy Boyle both by the Belgian authorities and in the highest social circles. To this end, I draw on the Belgiën correspondence in Vienna, in addition to the French and British diplomatic records and the manuscripts of the Duke of Leeds at the British Library.